2021
DOI: 10.1002/ange.202101460
|View full text |Cite
|
Sign up to set email alerts
|

Multinuclear Ag Clusters Sandwiched by Pt Complex Units: Fluxional Behavior and Chiral‐at‐Cluster Photoluminescence

Abstract: Multinuclear Ag clusters sandwiched by Pt complex units were synthesized and characterized by single crystal X‐ray diffraction and NMR studies. The sandwich‐shaped multinuclear Ag complexes showed two different types of fluxional behavior in solution: rapid slippage of Pt complex units on the Ag3 core and a reversible demetalation–metalation reaction by the treatment with Cl anion and Ag ion, respectively. The Ag2 complex obtained by demetalation reaction from the Ag3 complex displayed U to Z isomerization. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The molecule of Ag 3 ⊂ 1 comprises three unique silver(I) cations arranged into a cluster [65] in which each metal possessed a unique coordination environment. The Ag(1), closest to the pole, is bound to the three imine nitrogens (N(im)−Ag(1): 2.260(4)−2.398(4) Å) and the bridgehead atom (2.599(4) Å), whereas Ag(2) and Ag(3) remain in the equatorial part, coordinated by two pyrrolides (2.115(4) Å and 2.125(4) Å), and a pyrrolic (2.216(4) Å) and two imine nitrogens (2.229(4) Å and 2.519(4) Å), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The molecule of Ag 3 ⊂ 1 comprises three unique silver(I) cations arranged into a cluster [65] in which each metal possessed a unique coordination environment. The Ag(1), closest to the pole, is bound to the three imine nitrogens (N(im)−Ag(1): 2.260(4)−2.398(4) Å) and the bridgehead atom (2.599(4) Å), whereas Ag(2) and Ag(3) remain in the equatorial part, coordinated by two pyrrolides (2.115(4) Å and 2.125(4) Å), and a pyrrolic (2.216(4) Å) and two imine nitrogens (2.229(4) Å and 2.519(4) Å), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The Pt­(II) precursors 3 and 5 on the one hand and the Pt 2 Ag 2 complexes 9 and 11 on the other revealed identical absorption (266 nm) and emission patterns (397–411 and 431–436 nm at λ ex = 352 nm). The related known PtAg complexes were shown to undergo a blueshift, a redshift, or no change in their absorption/emission spectra upon the formation of a dative Pt → Ag bond. ,, …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a mixed-valence Pt 2 (II,IV) formulation with the metals linked by a Pt II → Pt IV donor−acceptor bond seems to be the most likely for 3a′ in MeCN solution, which is also compatible with the observed metal−metal coupling. 47 According to that, we observed that compound 3a′ reacted with MeI in acetonitrile to give 2a′. Keeping in mind the small energy barrier for the transformation of Int-R into Int′-R, the free energy difference between the species Pt 2 (III,III) (4a or 5a) and Pt 2 (II,IV) (Int′-Me, Int′-Bn) seems to determine the nature of the compounds obtained at r.t.…”
Section: Synthesis Of [{Pt(c^c* a )Bn(μ-pz)} 2 (μ-Br)]br (6a)mentioning
confidence: 79%